Pengaturan Tindak Pidana Pemalsuan Uang dalam Perspektif Kepastian Hukum - Winata, Rendy; Lasmadi, Sahuri; Erwin (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2026)
This study analyzes the regulation of the crime of counterfeiting from the perspective of legal certainty. Currently, the regulation is dualistic, with Law Number 7 of 2011 concerning Currency as the lex specialis and Law Number 1 of 2023 concerning the Criminal Code as the general provision. This dualism gives rise to various problems, such as unclear norms regarding the definitions of "counterfeiting" and "resembling," overlapping provisions, disparate criminal penalties, and the inability to regulate counterfeiting electronic money, counterfeit QRIS (Qualified Transaction Receipt System), cryptocurrency, and Artificial Intelligence-based counterfeiting. This normative legal research, using legislative, conceptual, and comparative analysis approaches, finds that regulatory policies do not provide adequate legal certainty. Harmonization of regulations is urgently needed to create clear criminal definitions, proportionate criminal penalties, and consistent law enforcement. This research is expected to provide comprehensive legislative policy recommendations to strengthen the protection of the Rupiah, increase the deterrent effect, and maintain national economic stability amidst rapid technological developments.